The Effect Of Employee Engagement In Change On The Effectiveness Of Organizational Transformation At PT XYZ - Nunu Fauzan Helwah; Elisa Anggraeni; Anggraini Sukmawati (Eduvest - Journal of Universal Studies, 2024)
PT XYZ is a telecommunications company that is focusing on massive organizational transformation. The results of the Employee Engagement Survey & Communication Effectiveness Survey in 2023 are lower than in 2020, the presumed impact of organizational transformation. The analysis of integration between employee engagement and change management has not been much studied, as most previous studies have researched independently. The objective of the research is to analyze the factors that influence employee engagement in change and the influence on organizational transformation effectiveness. 401 respondents were obtained with criteria of permanent employee and minimum working time of 2 years. Data were analyzed using descriptive statistics and SEM PLS. The results showed that change-related organizational resources, change-released job resources, change-related job demands, and personal resources have a significant positive impact on employee engagement in change, then employee engagement in change has a significant positive impact on the effectiveness of organizational transformation both directly and as a mediator.